Quantifying Museum Visitor Attention Using Bluetooth Proximity Beacons - Casano, Jonathan D.L (Archīum Ateneo, 2020)
This paper shows initial work on utilizing Bluetooth Low-Energy (BLE) beacons to uncover patterns in visitor paths and to determine the concentration of visitor attention within the Ateneo Art Gallery (AAG), the Philippines’ first museum of modern art. Participants carried phones instrumented with an application that logged distance estimates from BLE beacons deployed around the museum. The logs were then analyzed to produce scarf plots that visually represent paths taken. The results show the potential of BLE beacons for indoor location tracking. Aggregated visualization of similar scarf plots showed four notable patterns that provide insights on the museum areas that draw attention. The assumed usual route (pattern1: Start at 1st floor, go to 2nd floor then visit 3rd floor) was confirmed and an uncommon visiting pattern was discovered (pattern 2: Start at 3rd floor, go to 2nd floor, then visit 1st floor). It was also found that some visitors do not get to explore the entire museum (pattern 3: Some visitors only went to the 1st and 2nd floors. Pattern 4: Some visitors only went to the 2nd and 3rd floors). These insights can be used to make decisions regarding exhibit arrangement or museum layout design.